Significant association between a non-synonymous SNP in IGFBP5 gene and the growth of striped catfish (Pangasianodon hypophthalmus, Sauvage, 1878) - Tran, Trang Thi Huyen; Tran, Hoang Son; Le, Binh Thi Nguyen; Nguyen, Sang Van; Vu, Hai-Anh; Kim, Oanh Thi Phuong (Vietnam Journal of Biotechnology, 2023)
Insulin-like growth factor binding protein 5 (IGFBP5) is the highest conserved member of IGFBP family, and has the broad range of biological activities effecting on the cell growth. This study aims to investigate the association between genetic variation in IGFBP5 gene and the growth of striped catfish (Pangasianodon hypophthalmus). Single nucleotide polymorphisms (SNPs) were discovered and validated in IGFBP5 gene from two growth-selected populations (fast- and slow- growing fish). For SNP discovery, the fragments of IGFBP5 from sample sets of 10 fast- growing fish and 10 slow- growing fish were directly sequenced by Sanger sequencing. In this stage, 4 exonic SNPs were discovered, including a non-synonymous SNP 525 T>A (p. Val16Glu) in exon 1, and three synonymous SNPs (8859 G>A, 11713 C>A, 11992 T>C) in exon 4. The non-synonymous SNP 525 T>A (p.Val16Glu) was filtered to the next step of SNP validation. For validation, the SNP was individually genotyped in the test populations of 70 fast- growing fish and 70 slow- growing fish by single base extension method. Data analysis from the total SNPs which were collected from 80 fast- growing fish and 80 slow- growing fish indicated that non-synonymous SNP 525 T>A (p.Val16Glu) was significantly associated to the growth of striped catfish (p-value <0.001). Analysis of genetic diversity parameters (PIC, MAF) suggested that this SNP is a common variant, contributes significantly to the genetic variance. The non-synonymous SNP 525 T>A (p.Val16Glu) in IGFBP5 gene would become a SNP marker candidate for marker assisted selection (MAS) that can be used in pangasius breeding.